Supernumerary teeth in Necromys lasiurus (Rodentia, Cricetidae): the first record in Sigmodontinae - Simoes Libardi, Gustavo (2014)
There are several kinds of anomalies related to the teeth reported in mammals, and one of them is known as supernumerary teeth and is commonly noticed in the literature, being reported in nearly all orders of mammals. Here, we report the occurrence of supernumerary molars in the sigmodontine rodent Necromys lasiurus, a common and widespread small rodent of tribe Akodontini. In order to assess the patterns of morphometric variation of N. lasiurus in eastern South America, we examined the skulls of 1763 specimens. The supernumerary molars were found in 2 individuals, which represent a frequency of 0.11%. The origin of supernumerary teeth started a long discussion on tooth homology, whether this anomaly is a result of heredity, a mutation or an atavism. Based on the morphologies presented by the extra teeth encountered in N. lasiurus and on the evidences and hypothesis available in the literature, we consider that the presence of these supernumerary molars in one of the studied animals could be considered an atavism, and we also consider the extra molar presented by the other specimen is a malformation, due to some kind of random process occurred in later stages of the development of distal dental gem. To the best of our knowledge, this represents the first record of supernumerary molars in the subfamily Sigmodontinae and one of the few known cases in rodents.